Fun Vocabulary Learning: Peningkatan Kosakata Bahasa Inggris Siswa Sekolah Dasar melalui Board Game - Malabar, Fahria (Yayasan Daarul Huda Kruengmane, 2025)
Vocabulary is an important foundation in English language acquisition, especially in the primary school period as an early stage of foreign language learning. However, the still dominant learning using rote memorization makes students less motivated and limited in vocabulary acquisition. Therefore, innovative strategies are needed that are fun and encourage students’ active engagement. Game-based approaches (game-based learning) are believed to be capable of increasing learning interest while strengthening recall power towards vocabulary. This community service activity was implemented at Imam Shafi’i TPQ by involving primary school students. The main media used were board games with simple vocabulary themes such as colors, numbers, and animals. The activity stage consists of initial observation, game implementation, and evaluation. Observation shows that students are still limited in basic vocabulary and lack confidence. Through board games, students learn vocabulary with a competitive, collaborative, and fun atmosphere. Activity results showed there was a significant improvement, where students who were previously only able to name 2–3 vocabularies, after playing could name 6–8 vocabularies with more confidence. Additionally, students appear more enthusiastic, active, and motivated. Thus, the use of board games proved to effectively enhance vocabulary acquisition while fostering positive attitudes towards learning English early on.